Biomarker Optimization of Spinal Cord Stimulation Therapies. Issue 1 (3rd September 2020) - Nagel, Sean J.; Hsieh, Jason; Machado, Andre G.; Frizon, Leonardo A.; Howard, Matthew A.; Gillies, George T.; Wilson, Saul
Abstract: Objectives: We are in the process of designing and testing an intradural stimulation device that will shorten the distance between the location of the electrode array and the targeted neural tissue, thus improving the efficacy of electrical current delivery. Identifying a biomarker that accurately reflects the response to this intervention is highly valued because of the potential to optimize interventional parameters or predict a response before it is clinically measurable. In this report, we summarize the findings pertaining to the study of biomarkers so that we and others will have an up‐to‐date reference that critically evaluates the current approaches and select one or several for testing during the development of our device. Materials and Methods: We have conducted a broad survey of the existing literature to catalogue the biomarkers that could be coupled to intradural spinal cord stimulation. We describe in detail some of the most promising biomarkers, existing limitations, and suitability to managing chronic pain. Results: Chronic, intractable pain is an all‐encompassing condition that is incurable. Many treatments for managing chronic pain are nonspecific in action and intermittently administered; therefore, patients are particularly susceptible to large fluctuations in pain control over the course of a day. The absence of a reliable biomarker challenges assessment of therapeutic efficacy and contributes to either incomplete and inconsistent pain relief or, alternatively, intolerable side effects. Fluctuations in metabolites or inflammatory markers, signals captured during dynamic imaging, and genomics will likely have a role in governing how a device is modulated. Conclusions: Efforts to identify one or more biomarkers are well underway with some preliminary evidence supporting their efficacy. This has far‐reaching implications, including improved outcomes, fewer adverse events, harmonization of treatment and individuals, performance gains, and cost savings. We anticipate that novel biomarkers will be used widely to manage chronic pain.